Mechanical properties of foam sandwich with chopped‐glass‐fiber/carbon nanotube reinforced hierarchical structure interlayer. Issue 8 (29th May 2020) - Chen, Qihui; Du, Surui; Jiang, Zhiyuan; Liu, Yaqing; Du, Ruikui; Zhao, Guizhe
Abstract: A chopped‐glass fiber/multi‐walled carbon nanotubes (MWCNTs) hierarchical reinforcing structure was used to toughen the core‐face interlayer of sandwich materials. Chopped‐fiber mats modified by MWCNTs‐COOH were inserted at the face‐core interface before resin infusion. Sandwich beams were prepared by vacuum‐assisted resin transfer molding, containing a Polyvinylchloride (PVC) foam core covered with two glass fiber/epoxy composite face sheets. The mechanical properties were characterized using quasi‐static three‐point‐bending, Charpy impact, and asymmetric double cantilever beam. Improvement in mechanical properties and interlayer toughness was achieved in the sandwich structure with negligible weight increase and processing variations. The interfacial characteristics between chopped glass fibers, carbon nanotubes, and underlying energy absorption mechanisms were discussed and analyzed using scanning electron microscopy.